2023
DOI: 10.3390/s23031354
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Assessment of Functional Capacity through the Six-Minute Walk Test in Patients with Diabetes Mellitus Type 2: Validity and Reliability of Repeated Measurements

Abstract: A tele-assessed 6MWT (TL 6MWT) could be an alternative method of evaluating functional capacity in patients with diabetes mellitus type 2 (DM2). This study aimed to assess the validity and reliability of a TL 6MWT. The functional capacity of 28 patients with DM2 (75% men) aged 61 ± 13 years was evaluated twice via an indoor, center-based 6MWT (CB 6MWT) and twice outside each patient’s home via a web-based platform TL 6MWT. The study showed a high statistically significant correlation between the CB and TL 6MWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that supervised functional capacity assessments are reliable in clinical and home settings. Recently, remote assessment applications have been demonstrated in various populations, including people living with cancer, 17 those with mobility disorders, 14 individuals with mental health conditions, 15 people living with type 2 diabetes, 16 and community-dwelling older adults 11 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that supervised functional capacity assessments are reliable in clinical and home settings. Recently, remote assessment applications have been demonstrated in various populations, including people living with cancer, 17 those with mobility disorders, 14 individuals with mental health conditions, 15 people living with type 2 diabetes, 16 and community-dwelling older adults 11 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Web-based technologies, including gerontechnology, used at home, whether asynchronous or synchronous, have proven feasible and acceptable alternatives for community-dwelling older adults. 16 , 18 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they are becoming essential tools in Biomedicine and Bioengineering because of their ability to provide accurate, interactive, and immersive simulations of biological systems [ 88 ]. Thus, these technologies make it possible to deliver home-based assessments and interventions or telehealth, potentially offering cost-effective alternatives in several areas [ 59 , 89 ]. Furthermore, multiple practical applications are also emerging in sports sciences to increase the population’s PA levels through exergames, performance enhancement programs with technical or tactical training applications, and sports injuries recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Some AR and VR applications have demonstrated positive outcomes regarding the PA level [ 54 , 55 ]. For this purpose, VR has been used in healthy individuals [ 48 ] and in those with pathologies [ 39 , 56 , 57 , 58 , 59 ], as well as with different age groups [ 54 , 60 ], as active video games produce an energy expenditure equivalent to mild to moderate intensity PA [ 46 ].…”
Section: Introductionmentioning
confidence: 99%